Structural determination of the cell wall polysaccharide LCPS-1 in Lacticaseibacillus paracasei strain Shirota YIT 9029. (November 2022) - Mizukoshi, Harumi; Kimura, Kazumasa; Ikemura, Haruo; Mori, Yoko; Nagaoka, Masato
Abstract: The neutral polysaccharides LCPS-1 and LCPS-2 play functional roles in the cell wall of the lactic acid bacterium Lacticaseibacillus paracasei strain Shirota YIT 9029 (LcS; formerly Lactobacillus casei strain Shirota YIT 9029), which has long been used as a probiotic food product. Studies have shown that LCPS-1 is associated with the immunomodulatory functions of LcS. We hypothesized that the structure of LCPS-1 is crucial for elucidating the mechanism of action of LcS on host immune responses and aimed to solve the undetermined primary structure of LCPS-1. Our results showed that LCPS-1 has a molecular weight of >400 kDa and is composed of Glc, Rha, Gal, and GlcNAc, with a repeating structure. Using limited degradation reactions, including controlled Smith and deamination degradations, we obtained key fragments with low molecular weight. Subsequently, their structures were analyzed using NMR spectra and other analytical techniques. Further, we integrated the results for each key fragment to derive the complete structure of LCPS-1. Our results indicated that the most probable structure of LCPS-1 is composed of two types of units (X, Y), each with a basic structure of seven sugars in which the C2-position of Rha is substituted with an acetyl group. The structure of X is 6[Glcβ1-2] Galα1-3[2-OAc] Rhaβ1-4Glcβ1-4[Rhaα1-3] [Glcα1-6] Glcβ1- and that of Y is 6[Glcβ1-2] Galα1-3[2-OAc] Rhaβ1-4Glcβ1-4[Rhaα1-3] [Glcα1-6)] GlcNAcβ1-, which can be expressed as (X6 Y12 )n . In this study, we identified the primary structure of LCPS-1, and our results may enable an improved understanding of the immunomodulatory abilities of LcS. Graphical abstract: Image 1 Highlights: LCPS-1 is a polysaccharide of Lacticaseibacillus paracasei strain Shirota (LcS). Herein, the primary structure of the cell wall polysaccharide LCPS-1 was assessed. LCPS-1 is composed of seven sugars and typically repeating units. Characteristically, O -acetyl is bound to the 2-position of β-Rha. These finding can help elucidate the immunomodulatory function of LcS.